Development of Students’ Informal Reasoning across School Level - Ari Widodo; Dwie Saptarani; R. Riandi; Diana Rochintaniawati (Journal of Education and Learning (EduLearn), 2017)
Informal reasoning is the basic reasoning frequently used by most people to solve complex daily life problems. Unlike scientific reasoning, informal reasoning includes cognitive and affective processes that the types of reasoning can be intuitive, emotive and rational. This cross sectional study describes the development of students’ informal reasoning at elementary school, junior high school, and senior high school. Moreover, the study also identifies differences between boys and girls reasoning. Participants are 20 elementary school students, 30 junior high school students, and 30 high school students who attend schools managed by the same foundation. Data were collected using five items test on issues found in everyday life. Students’ responses were grouped into intuitive, emotive, or rational reasoning. The results suggest that students’ informal reasoning tend to develop parallel to the school grade. Related to gender, the study finds that girls tend to use rational reasoning while boys tend to use intuitive reasoning.